1997
DOI: 10.1076/ceyr.16.6.534.5079
|View full text |Cite
|
Sign up to set email alerts
|

Changes in corneal and lens autofluorescence and blood glucose levels in diabetics: parameters of blood glucose control

Abstract: Results suggest that lens autofluorescence might represent the long-term control of diabetes, and corneal autofluorescence levels may represent short-term changes in the blood glucose level, because hyperglycemia accelerates with increasing corneal autofluorescence in PDR patients. Corneal and lens autofluorescence may be related to the breakdown of the blood-aqueous barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 18 publications
0
29
1
Order By: Relevance
“…17 In the present study, although the sample number was small, no pattern of diurnal variation was found in normal controls, and …”
Section: Pormentioning
confidence: 85%
“…17 In the present study, although the sample number was small, no pattern of diurnal variation was found in normal controls, and …”
Section: Pormentioning
confidence: 85%
“…Indeed, there is a positive correlation between HbA1c and fasting blood plasma glucose levels, and separately corneal autofluorescence (Koefoed et al, 1996). High serum glucose concentrations also result in high aqueous glucose levels, especially after the breakdown of the blood-aqueous barrier, which is reported to occur in diabetic patients (Mori et al, 1997). High glucose levels in the aqueous may increase the non-enzymatic glycation of corneal proteins and collagen, thereby increasing the fluorescence of the cornea.…”
Section: Discussionmentioning
confidence: 97%
“…We previously showed that corneal autofluorescence values measured using a commercial fluorophotometer significantly increased in patients with proliferative diabetic retinopathy (PDR) (9). Moreover, we reported that lens autofluorescence values using our fluorophotometer were significantly correlated with AGE levels in extracted lenses in diabetic animal models (10).…”
mentioning
confidence: 97%